The influence of HLA-DRB1*15 on motor cortical pathology in multiple sclerosis. - Yates, R; Esiri, M; Palace, J; Mittal, A; DeLuca, G (2014)
AIM: Multiple Sclerosis (MS) is a common and heterogeneous CNS inflammatory demyelinating disease. The HLA-DRB1 locus may influence clinical outcome. MS cortical pathology is frequent and correlates with measures of clinical disability, including motoric dysfunction that is a predominant feature of disease progression. The influence of HLA-DRB1*15 on motor cortical pathology is unknown. METHODS: A pathologically confirmed age- and sex-matched HLA-DRB1*15+ (n=21) and HLA-DRB1*15- (n=26) MS post-mortem cohort was used for detailed pathologic analyses. For each case, adjacent sections of motor cortex were stained for myelin and inflammation, to evaluate the extent and distribution of motor cortical pathology. A subset of MS cases (n=42) had spinal cord (SC) pathologic outcome data available for comparison. RESULTS: Motor cortical demyelination was more pronounced in younger cases (r =-0.337, p < 0.05), with MS cases carrying the HLA-DRB1*15 allele driving this effect (r=-0.612, p < 0.01). HLA-DRB1*15+ MS cases had more severe motor cortical parenchymal (p < 0.05), perivascular (p < 0.05), and meningeal (p < 0.05) T-cell inflammation compared to HLA-DRB1*15- cases. HLA-DRB1*15 status significantly influenced the extent of motor cortical microglial burden in both NAGM (p < 0.0001) and lesions (p < 0.01) in MS cases. Relationships between the extent of motor cortical and SC pathology were limited, but when present were primarily driven by HLA-DRB1*15+ cases. CONCLUSION: HLA-DRB1*15 status has a significant association with the extent of inflammation in the MS motor cortex, the extent of demyelination in younger MS cases, and influences relationships between motor cortical and SC pathology.